2021
DOI: 10.1101/2021.11.29.466909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The HUSH complex controls brain architecture and protocadherin fidelity

Abstract: Fine-tuning of neural connectivity is important for cerebral functions and brain evolution. Protocadherins provide barcodes for neuronal identity as well as synapse formation and expansion of protocadherin cluster genes has been linked to advanced cognitive functions. The tightly controlled stochastic and combinatorial expression of the different protocadherin isoforms in individual neurons provides the molecular basis for neuronal diversity, neuronal network complexity and function of the vertebrate brain. Ho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…They also prevent the synthesis of retroviral envelope proteins that are particularly involved in neurodegeneration (Turelli et al, 2020). Finally, in a Morc2 KO mouse model, the overexpression of the protocadherin cluster has been associated with a loss of neuromuscular functions (Hagelkruys et al, 2021). In the same study, a Mpp8-Morc2 double KO mouse model was shown to develop the same phenotype than the Morc2 KO and the Mpp8 KO mice, suggesting that a common pathway (the HUSH complex) is responsible for the phenotype.…”
Section: Transcriptional Regulationmentioning
confidence: 91%
See 2 more Smart Citations
“…They also prevent the synthesis of retroviral envelope proteins that are particularly involved in neurodegeneration (Turelli et al, 2020). Finally, in a Morc2 KO mouse model, the overexpression of the protocadherin cluster has been associated with a loss of neuromuscular functions (Hagelkruys et al, 2021). In the same study, a Mpp8-Morc2 double KO mouse model was shown to develop the same phenotype than the Morc2 KO and the Mpp8 KO mice, suggesting that a common pathway (the HUSH complex) is responsible for the phenotype.…”
Section: Transcriptional Regulationmentioning
confidence: 91%
“…In mouse, Morc2 expression is dynamic during development with a peak of expression in early phases followed by a decrease during aging (Sancho et al, 2019). Morc2 is highly expressed in the brain, exclusively in neurons, and a Morc2 KO in mice is lethal at embryonic day 13.5 (Hagelkruys et al, 2021). Altogether, these observations suggest a critical role of MORC2 during development especially in the brain.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Given the essential role of MORC2 for the HUSH complex activity 28,43 , this suggests that the HUSH-SETDB1-MORC2 repression complex acts as a major epigenetic regulatory entity to maintain HSV-1 latency in neurons. SETDB1 is known for its major involvement in neurons survival and brain development 44 , and the role of HUSH-MORC2 in developmental aspects of the CNS has recently been put to the limelight 45 . The involvement of the HUSH-SETDB1-MORC2 entity in the acute control, then long-term maintenance, of the latency of a neurotropic virus is thus of particular interest.…”
Section: Discussionmentioning
confidence: 99%